Incorporating complementary ratios in the analysis of financial statements - Trigueiros, D. (Accounting, Management and Information Technologies, 1994)
Ratios are routinely used for extracting information from accounting reports. However, ratios present only part of the information available and can be easily complemented provided that information-technology facilities are accessible. This study infers the functional form of the information discarded by ratios. Then it develops extensions of ratios incorporating the discarded information, showing examples of their use and discussing the benefits obtained. Extensions of ratios seem promising as a facility attached to computerized databases of accounting reports. The concepts developed here are a step toward a more technology-supported analysis of financial statements.